FINANCIAL ACCOUNTING STANDARDS NO. 133: HEDGE ACCOUNTING RULES FOR U.S. FIRMS - Bierman Jr., Harold (Assurances)

(untitled) (HEC Montréal, 1999)
ln June 1998 the Financial Accounting Standards Board published FAS 133 Accounting for Derivative Instruments and Hedging Activities. The Standard defines three fundamental accounting rules that significantly modify the accounting pratices of U.S. firms. The three rules are: 1. All derivatives should be reported on statements of financial position. 2. All derivatives should be reported at fair value. 3. Accounting for changes in the values of derivatives depends on the use of the derivative and whether it qualifies for hedge accounting. The details of applying this third rule is likely to lead to extensive discussions regarding the cost and the benefits of specific provisions of FAS 133.